Особливості росту і розвитку деяких видів злаків та Betonica officinalis L. у штучних рослинних угрупованнях - Кохан, Т.П. (Промышленная ботаника, 2013)
Приведены результаты исследований особенностей роста и развития двух видов злаков (Poaceae) Arrhenatherum elatius (L.) J. Presl et C. Presl, Phleum phleoides (L.) H. Karst. и Betonica officinalis L. (Lamiaceae). В результате исследований было установлено, что совместное произрастание с B. officinalis не оказывает влияния на рост и развитие P. phleoides и оказывает слабое влияние при достижении генеративной фазы на рост и развитие A. elatius (в частности на висоту и формирование биомассы). Также исследуемые злаки замедляют рост и развитие B. officinalis на несколько лет в фазе вегетации, а в генеративную фазу развития ее растения вступают только на седьмой год жизни. Полученные данные имеют теоретическое значение для изучения взаимоотношений видов, а также прикладное – для восстановления растительного покрова степей. The paper presents results of the studies on growth and development features of two grass species (Poaceae) – Arrhenatherum elatius (L.) J. Presl et C. Presl and Phleum phleoides (L.) H. Karst., and Betonica officinalis L. (Lamiaceae). It is established that the growth and development of Ph. phleoides growing in association with B. officinalis is not retarded, and those of A. elatius are insignificantly affected on reaching the generative phase (namely on the plant height and above-ground mass). The study has also shown that these grasses decelerate the growth and development of B. officinalis L. for a few years in the vegetative phase and this plant reaches the generative phase of its development only in the seventh year. These data are of theoretical importance for the studies of plant interrelations and of practical importance for restoration of steppe vegetation.